Analisis Pelaksanaan Inventarisasi Dan Identifikasi Validasi Data Pemanfaatan Tanah Perusahaan Di Kabupaten ogan komering ilir - Syaparman, Syaparman; Iriani, Atrika; Haryanto, Meilan (@-Publik: Jurnal Administrasi Publik, 2022)
This study aims to analyze the implementation of the inventory and identification of the company's land use in Ogan Komering Ilir Regency. This research is a descriptive qualitative research, which is a type of research designed to collect information about these symptoms. The conclusions of this study are as follows: (1). In general, the inventory of Ogan Komering Ilir (OKI) employees and the detection of the company's land use data validation are optimal and in accordance with the Ogan Komering Ilir Regent's Regulation No. 6. The inventory and detection team of land use data validation in Ogan Komering Ilir Regency. Year 2020. (2). In particular, the implementation of the inventory and identification of the company's land use in Ogan Komering Ilir Regency went well, starting from planning with target indicators, regulations, infrastructure and implementation time, as well as APBD funds, personal indicators available to organizers, a. 7 people in total. , organizational structure and division of labor according to the applicable regulations, namely the regulation of the OKI Regent, so both the inventory of company use and detection of data validation of the OKI Regent's company land use are carried out properly. conduct field inspection data audits to validate data submitted by factory companies operating in the Ogan Komering Iliri area, and the stages of external control and internal control. conduct an inventory and identification of land use data validation of companies in Ogan Komering Ilir Regency.